THE FORM AND FUNCTION OF SLANG EXPRESSIONS ON THE THREAD SOCIAL MEDIA (@MedanTalkViral) - Harahap, Annisah Inriani (ELP (Journal of English Language Pedagogy), 2024)
This research examined the dynamic evolution of slang in the context of Medan, exploring its formation, diverse expressions, and functions in everyday interactions. It focused on the comment section of the @Medantalkviral account on the Thread platform. The study employed Yanchung and Yanhong (2013) elaboration theory, supported by Fisherman (1972), to understand the meanings of slang expressions. The approach examined how these expressions were articulated in texts, whether fully or partially, in order to gain a nuanced understanding. Using observation and recording techniques, including screenshots, the data consisted of words and comments from Medan residents via the social media account @Medantalkviral. The analysis employed analogy and intralingual methods, revealing 12 newly invented slang expressions on social media. The results showed a variety of slang forms, including words, phrases, clauses, and sentences, with identified linguistic functions such as identity, kinship/politeness, emotional expression, directive function, and referential function. This study contributed to a broader understanding of linguistic phenomena in the digital age and the multifaceted nature of slang in social interactions.